2023
DOI: 10.3389/fpubh.2023.1105428
|View full text |Cite
|
Sign up to set email alerts
|

Appearance anxiety and social anxiety: A mediated model of self-compassion

Abstract: BackgroundPrevious studies have focused on the comorbidity of appearance anxiety and social anxiety, but few studies have focused on the protective role of self-compassion as underlying this mechanism, in young people like University students. With the increase of prevalence of appearance anxiety and social anxiety in this age group, it is necessary to explore factors that can buffer against the symptoms of these disorders. Therefore, the aims of this study were to research the effect of appearance anxiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…In the analysis of studies about the mediating effect of social anxiety, the effect values were found to range from 7.18 to 37% [ 78 , 79 ], both of which were considered to provide new intervention strategies for predicting college students’ social behaviors and ameliorating social anxiety. The mediating effect accounted for less in the present study, which is similar to the results of recent effect analyses on the effect of self-compassion-mediated appearance anxiety on social anxiety [ 72 ], but it also confirms the theoretical validity of the theoretical model, which implies that self-efficacy and self-esteem represent a potential mechanism of action that can partially explain the relationship between appearance anxiety and social anxiety. In other words, increasing self-efficacy and self-esteem as a way to improve self-perception may help alleviate social anxiety among college students.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the analysis of studies about the mediating effect of social anxiety, the effect values were found to range from 7.18 to 37% [ 78 , 79 ], both of which were considered to provide new intervention strategies for predicting college students’ social behaviors and ameliorating social anxiety. The mediating effect accounted for less in the present study, which is similar to the results of recent effect analyses on the effect of self-compassion-mediated appearance anxiety on social anxiety [ 72 ], but it also confirms the theoretical validity of the theoretical model, which implies that self-efficacy and self-esteem represent a potential mechanism of action that can partially explain the relationship between appearance anxiety and social anxiety. In other words, increasing self-efficacy and self-esteem as a way to improve self-perception may help alleviate social anxiety among college students.…”
Section: Discussionsupporting
confidence: 90%
“…Some scholars have suggested that appearance anxiety may also be triggered by social anxiety [ 70 ], while others have argued that fear of negative evaluations mediates the link between appearance anxiety and social anxiety [ 71 ]. Additionally, previous studies have found that self-compassion [ 72 ], perfectionism [ 73 ], and social rejection sensitivity [ 21 ] are also present and work to produce a relationship between the two. However, no studies have been found to longitudinally examine the causal relationship between appearance anxiety and social anxiety, and these are a focus for future research.…”
Section: Discussionmentioning
confidence: 99%
“…A higher total SASS score indicated a higher degree of social anxiety. The Chinese version of SASS had good reliability and validity in some previous studies ( 22 , 44 ), with a Cronbach’s alpha of 0.76 in the current study.…”
Section: Methodssupporting
confidence: 66%
“…Similarly, an increasing number of researchers have noted that the place of residence is also an influencing factor of the three variables mentioned above. Specifically, compared to rural adolescents, urban adolescents may have a higher level of social anxiety ( 44 ) and a higher prevalence of Internet addiction ( 40 ). However, according to two sample-based mortality surveillance systems of suicide rates in China, the incidence rate ratio (IRR) of suicide rates in rural areas (IRR = 1.93, 95% CI: 1.84–2.03) is higher than that in urban areas ( 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…Appearance anxiety (AA) refers to a condition when an individual is overly concerned about their appearance. They may become unconfident and anxious about their appearance when they perceive social standards or poor evaluations of themselves from others ( Gao et al, 2023 ). With the increasing rate of science and technology development, various social platforms and media have become flourishing and have been invading in college students’ lives ( de Vries et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%